Who is a "knowledge worker" - clarifying the meaning of the term through comparison with synonymous and associated terms = Kim jest ?pracownik wiedzy? - wyjaśnianie znaczenia pojęcia poprzez porównanie z terminami bliskoznacznymi i powiązanymi - Surawski, Bartosz (Zielona Góra: Faculty of Economics and Management Press)
The term "knowledge worker" has entered the language of management and economics, becoming popular or even fashionable. Consequently, its definitions are varied and often ambiguous or provisional - which makes it difficult to identify and research such employees. Deeper understanding of the term "knowledge workers" is required.
Keywords: pracownicy wiedzy; praca oparta na wiedzy; specjaliści; profesjonaliści; ISCO; knowledge worker; knowledge work; specialist; professionals